Performance Analysis of Various Phases of SRM with Classical and New Compact Converter - S.M. Mohamed Saleem; L. Senthil Murugan (Institute of Advanced Engineering and Science, 2015)
In recent years, considerable attention has been given to find the compact and low cost power converter topology for Switched Reluctance Motor (SRM) drive to meet the emerging applications such as plotters, fans, pumps, screw rotary compressor drives, high speed application drives above 30,000 RPM. This paper is concerned with such as attempt to formulate a new compact power converter for SRM drive. The proposed power converter has reduced number of power electronic components which makes the converter compact and also reduce the switching losses. The power factor plays a vital issue in the usage of power electronic converters. The power boost converter and PI controller. A Simulink system is developed for 3Φ SRM by using MATLAB software. The proposed converter performance is compared with the classical converter and analysis results are presented.